Aerobic Dehydrogenative Heck Reactions of Heterocycles with Styrenes: A Negative Effect of Metallic Co‐Oxidants. Issue 1 (23rd December 2012) - Vasseur, Alexandre; Harakat, Dominique; Muzart, Jacques; Le Bras, Jean
Abstract The aerobic dehydrogenative Heck reaction (DHR) of heterocycles with styrenes was found to be more efficient in the absence of metallic co‐oxidants. According to a study of the isotope effect, the CH cleavage was the rate‐determining step of the catalytic cycle. Electrospray ionization mass spectrometry, subsequent MS/MS, and high‐resolution mass spectrometry were used to detect and characterize catalytic intermediates and species formed in the presence of metallic co‐oxidants.